Communicative Model of Presidential Chief of Staff in Decision Making of Public Policy - Henni Gusfa; Gun Gun Heryanto; Tuti Widiastuti; Rita Nurlita Setia; Yofrina Octika Gultom (Nyimak: Journal of Communication, 2021)
This research examined the communicative institution of the presidential chief staff of the Republic of Indonesia during Jokowi’s administration.  The purpose of this research was to find a communicative model applied by the presidential chief staff in making public decisions. The theory used was the role of Communicative Constitutive of Organization, the management concept of bureaucracy and public office, and the rational model of public decision making.  The method used in this research was case study in which cases analyzed from policies through interview and observation, and literature study. The results of the research on decision-making processes of public policies based on national development planning in Jokowi’s Nawacita were institutional communications carried out by the Presidential Chief of Staff (PCS) in the form of monitoring, solving barriers related to bureaucracy management in communication toward public through various online media, talk shows, and news. Communication across institutions and internal communication were carried out exclusively. Based on rational decision making, the communicative model of the presidential chief of staff was one-way process providing no room for discussion or negotiation involving the community.  stakeholder external  participation in the institutional communicative model were in ministry department, non-institutional department, provincial, district, and city governments.Keywords: Model, communicative, presidential, public policy, decision making ABSTRAKStudi ini mengkaji kelembagaan komunikatif para staf Kepala Kepresidenan Republik Indonesia pada masa pemerintahan Jokowi. Tujuan dari penelitian ini adalah untuk mengetahui model komunikatif yang diterapkan oleh jajaran pimpinan presiden dalam pengambilan keputusan publik. Teori yang digunakan adalah peran Konstitutif Komunikatif Organisasi, konsep manajemen birokrasi dan jabatan publik, dan model rasional pengambilan keputusan publik. Metode yang digunakan dalam penelitian ini adalah studi kasus di mana analisis kasus dari kebijakan melalui wawancara dan observasi, serta studi pustaka. Hasil penelitian proses pengambilan keputusan kebijakan publik berdasarkan perencanaan pembangunan nasional dalam Nawacita Jokowi adalah komunikasi kelembagaan yang dilakukan oleh Kepala Staf Kepresidenan (PCS) dalam bentuk pemantauan, penyelesaian hambatan terkait pengelolaan birokrasi dalam komunikasi menuju publik melalui berbagai media online, talk show, dan berita. Komunikasi lintas institusi dan komunikasi internal dilakukan secara eksklusif. Berdasarkan pengambilan keputusan yang rasional, model komunikatif Kepala Staf Kepresidenan merupakan proses satu arah yang tidak memberikan ruang untuk diskusi atau negosiasi yang melibatkan masyarakat. Partisipasi eksternal pemangku kepentingan dalam model komunikatif kelembagaan berada di departemen kementerian, departemen non-kelembagaan, pemerintah provinsi, kabupaten, dan kota.Kata Kunci: Model, komunikatif, presidensial, kebijakan publik, pengambilan keputusan